Phase I study of anti-epidermal growth factor receptor antibody-drug conjugate serclutamab talirine: Safety, pharmacokinetics, and antitumor activity in advanced glioblastoma. Issue 1 (21st December 2022) - Carneiro, Benedito A; Papadopoulos, Kyriakos P; Strickler, John H; Lassman, Andrew B; Waqar, Saiama N; Chae, Young Kwang; Patel, Jyoti D; Shacham-Shmueli, Einat; Kelly, Karen; Khasraw, Mustafa; Bestvina, Christine M; Merrell, Ryan; et al.
Abstract: Background: Serclutamab talirine (Ser-T, formerly ABBV-321) is an antibody-drug conjugate consisting of an antibody (AM-1-ABT-806) directed against activated epidermal growth factor receptor (EGFR) and a pyrrolobenzodiazepine dimer. We investigated Ser-T monotherapy in a phase I, first-in-human, dose-escalation, and dose-expansion study in patients with advanced solid tumors associated with EGFR overexpression. Methods: Eligible patients (≥18 years) had advanced, histologically confirmed solid tumors associated with EGFR overexpression (centralized testing). Patients received Ser-T intravenously once every 4 weeks (Q4W; 5–50 μg/kg) in the dose-escalation phase. Herein, preliminary antitumor activity at the recommended phase II dose (RP2D) is reported only for patients with glioblastoma ( n = 24); additional assessments included all treated patients. Results: Sixty-two patients (median age: 58 years) were enrolled within the dose-escalation ( n = 43) and dose-expansion ( n = 19) phases. One dose-limiting toxicity, grade 3 aspartate aminotransferase and alanine aminotransferase elevation, occurred at 20 μg/kg during dose escalation. The Ser-T RP2D regimen of 50 μg/kg × 1 (loading dose) followed by 25 μg/kg Q4W (maintenance dose) was administered during dose expansion. Fatigue (37%) was the only treatment-emergent adverse event (AE) occurring in >25% of patients. Two patients (3%) reported mild treatment-related ocular AEs (eye pruritus). Responses in patients with glioblastoma included 1 partial response ( 33 months), 6 stable disease, and 14 progressive disease (not evaluable: n = 3). Conclusions: Ser-T monotherapy at doses up to 50 μg/kg initial dose, followed by 25 μg/kg Q4W demonstrated a tolerable safety profile with minimal antitumor activity observed in patients with glioblastoma. The glioblastoma dose-expansion cohort was closed due to a lack of efficacy (NCT03234712).